Praktik Sosial: Kebudayaan Desa Kemiren Banyuwangi Sebagai Desa Wisata Adat - Febriyan Dwi Rachman; Intan Syah Fitri; Vindy Febita Mamangkey (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Society always experiences critical periods in social life. This critical situations raises people’s trust in everything that is metaphysical as an alternative to solving problems in their social life. Rural communities, especially the people of Banyuwangi, are very thick with cultural values and spritual beliefs that are influenced by osing customs as a history of Blambangan. This study aims to analyze the habitus, capital realm, and social practices of the Kemiren Village community related to culture. This study uses a qualitative method with an ethnographic approch to understand the social setting of Kemiren village. The theory used in this study is sosial practice theory from Pierre Bordieu. The locatin of this research was conducted in the Kemiren Traditional Tourism Village, Banyuwangi regency. The subjects of this research are the community and customary stakeholders who act as cultural agents in customary and cultural social practices. The results of this study indicate that the habitus of the Kemiren village community in carrying out varios traditional rituals. The habitus of community rituals is influenced by internalization and socila structure in the meaning of cultural values carried out by the Kemiren village community. The dominant village community capital and cultural agent is social capital. Cultural agents and the village community have good realtions that are able to create economic benefits and recognition from the Tourism Office and Banyuwangi Goverment.